Development of RP HPLC method for aminocaproic acid determination in a complex nasal drug - Nefedova, Lilia; Sahaidak-Nikitiuk, Rita; Blazheyevskiy, Mykola; Barnatovych, Svetlana (ScienceRise: Pharmaceutical Science, 2020)
The aim of this work was to develop a method of RP HPLC for the quantitative determination of aminocaproic acid in a complex nasal drug. Materials and methods. A solution of aminocaproic acid and a solution of a complex model mixture containing aminocaproic acid were used for the study purposes. A method used for sample preparation was derivatization of aminocaproic acid with dansyl chloride. A method of quantitative determination was RP HPLC analysis with UV detection at 288 nm. Results. The obtained data confirm the specificity, linearity, and correctness of the method proposed for quantitative analysis. Therewith, the correlation coefficient, limit of detection, limit of quantification and relative standard deviation (RSD) are R=0.9998, LOD=4.6·10-5 g/mL, LOQ=1.4·10-4 g/mL, and RSD=1.16% respectively. Conclusions. A method of RP HPLC for the quantitative determination of aminocaproic acid in a complex nasal drug has been developed and its validation assessment has been carried out according to the following validation parameters: specificity, accuracy, linearity, and precision (repeatability). Statistical processing of the obtained results shows that all the validation parameters studied are within the acceptance criteria